THE EFFECT OF GOOD CORPORATE GOVERNANCE AND FINANCIAL DISTRESS ON REAL EARNINGS MANAGEMENT - Santi Yopie; Erika - Erika (UNIB Press, 2021)
This research aims to analyze the effect of good corporate governance and financial distress on real earnings management. The sample in this study is a manufacturing company listed on Indonesia Stock Exchange for the 2016-2020 period. Data collection in this study was carried out using secondary data taken from the company's financial statement. The data were analyzed and tested using the SPSS 25 program to test descriptive statistics and outlier tests. The Smart PLS 3.0 program was used to test validity and reliability, test quality indexes, and test hypotheses. The results of this study indicate that institutional ownership has a significant effect on real earnings management, managerial ownership has no significant effect on real earnings management, family ownership has no significant effect on real earnings management, the audit committee has a significant effect on real earnings management, audit quality has a significant effect on management. Financial distress has a significant effect on real earnings management. The moderating variable in this study proves that family ownership has no significant effect on real earnings management which is moderated by political connections.